The Influence of Managerial Ownership, Institutional Ownership, and Leverage on Dividend Policy (Case Study of Food and Beverage Companies Listed on The IDX for The 2017-2021 Period) - Praduana, Veradela Restu; Rinofah, Risal; Maulida, Alfiatul (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to determine and analyze the influence of managerial ownership, institutional ownership, and leverage variables on dividend policy. The population is food and beverage companies on the Indonesia Stock Exchange for the 2017-2021 period. The sample of this research was determined by sampling method based on the criteria of companies listed on the Indonesia Stock Exchange (IDX) and the publication of complete reports and data including data from variables that have been studied during the 2017-2021 research period. This research uses quantitative data with multiple linear regression techniques. The research sample was determined using a purposive sampling technique and resulted in a sample of 20 companies. Quantitative analysis includes classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), multiple linear regression test, model feasibility test via t-test, F test, and coefficient of determination. Based on the research results, show that managerial ownership does not affect dividend policy, institutional ownership has a positive effect on dividend policy, and leverage has a positive effect on dividend policy. Based on the research results that have been explained, it can be concluded that managerial ownership has no effect on dividend policy, and institutional ownership and leverage have a positive effect on the dividend policy of food and beverage companies listed on the IDX for the 2017-2021 period.